G-Protein-Gated Inwardly Rectifying Potassium (GIRK) Channel Subunit 3 Knock-Out Mice Show Enhanced Ethanol Reward - Tipps, Megan E. (Alcohol Clin Exp Res, 2016)
BACKGROUND: G protein-coupled inwardly rectifying potassium (GIRK) channels contribute to the effects of a number of drugs of abuse, including ethanol. However, the roles of individual subunits in the rewarding effects of ethanol are poorly understood. METHODS: We compare conditioned place preference (CPP) in GIRK3 subunit knock-out (GIRK3(−/−)), heterozygote (GIRK3(+/−)), and wild-type (WT) mice. In addition, the development of locomotor tolerance/sensitization and the effects of ethanol intoxication on associative learning (fear conditioning) are also assessed. RESULTS: Our data show significant ethanol CPP in GIRK3(−/−) and GIRK3(+/−) mice, but not in the WT littermates. In addition, we demonstrate that these effects are not due to differences in ethanol metabolism, the development of ethanol tolerance/sensitivity, or associative learning abilities. While there were no consistent genotype differences in the fear conditioning assay, our data do show a selective sensitization of the impairing effects of ethanol intoxication on contextual learning, but no effect on cued learning. CONCLUSIONS: These findings suggest that GIRK3 plays a role in ethanol reward. Further, the selectivity of this effect suggests that GIRK channels could be an effective therapeutic target for the prevention and/or treatment of alcoholism.